Modifying compliance behavior to diet, medication and activity of daily living to uncomplicated M.I. patients - Palermo, Ma. Fe N.
Rehabilitation is a continuous, dynamic process. The patient is seen as a whole person in the process of healing or entering into a functioning society within the limits of his ability. To enhance his capacities, his cognitive level on what the disease is all about and how he can participate in the plan of care can entice his cooperation towards self-reliance. The quantity and quality of life can be improved through the interplay of the patient's social support system. Philippine Health Statistics reported increasing incidence and mortality of heart diseases. It ranked 4th in 1968, 3rd in 1978 and 2nd in 1986. These findings proved to be a national threat both in economy and family solidarity because death is sure. This study sought to determine the efficacy of a learning module implemented by the continuing care nurse in modifying compliance behavior to uncomplicated MI patients. Positive health behaviors develop self-reliance and therefore maintains the psychologic integrity. Likewise recurrences are prevented and quality of life is insured. This intervention strategy was applied to 12 uncomplicated MI patients who were confined and discharged from 1 of the following hospitals: United Doctors Medical Center, East Avenue Medical Center, Quezon City General Hospital and Far Eastern University Medical Foundation. Consents from patient, family and physician were sought 1st before home visit was done. To determine the significance of the experiment, the data were analyzed through the use of the T-test preset at p .05 level of significance. To determine the correlation of knowledge to compliance and compliance to variables like age, sex, civil status, monthly income and educational attainment. Data were subjected to the Pearson Product Moment Correlation. The level of significance was also preset at p .05. The study yielded these important findings: 1. Result of pre and post test scores showed significant difference at .001 level. There is an increase in the cognitive level of MI patients to heart and heart attack, medication, diet and activities after the implementation of the learning module by the continuing care nurse. 2. There is a significant correlation between overall gained knowledge and compliance. 3. There is no significant correlation between compliance and age, sex, civil status and monthly income. 4. There is an inverse correlation between compliance and educational attainment.